Writing of scientific papers based on artificial intelligence at Sekolah Tinggi Ilmu Syariah Hidayatullah Balikpapan - Zulkarnain, Zulkarnain; Mahfud, Tuatual; Karim, Syarul; Amsal, Andi Yasir; Aditya, Angga Wahyu; Mahsun, Mahsun; Kusuma, Bambang Jati; Kango, Riklan; Gozali, Gozali (Jurnal Hasil Inovasi Masyarakat, 2025)
This community service activity aims to increase the capacity of lecturers and students of STIS Hidayatullah Balikpapan in utilizing Artificial Intelligence (AI) technology for writing scientific papers effectively, efficiently, and ethically. Activities are carried out in the form of interactive workshops consisting of lectures, demonstrations, hands-on practice, and mentoring. Participants consisted of 35 people, including lecturers and students. The results of the evaluation showed that participants succeeded in creating scientific articles using AI, as well as understanding the use of AI by prioritizing the ethics of writing AI-based scientific papers. This training is expected not only to improve students' skills in using technology, but also encourage the development of student adaptation to the increasingly rapid development of information technology. Thus, this training is expected to be a model for other universities in facing the AI technology revolution.